2020
DOI: 10.1101/2020.03.26.009217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-domain dynamics drive cholesterol transport by NPC1 and NPC1L1 proteins

Abstract: Transport of LDL-derived cholesterol from lysosomes into the cytoplasm requires NPC1 protein; NPC1L1 mediates uptake of dietary cholesterol. We introduced single disulfide bonds into NPC1 and NPC1L1 to explore the importance of inter-domain dynamics in cholesterol transport. Using a sensitive method to monitor lysosomal cholesterol efflux, we find that NPC1's N-terminal domain need not release from the rest of the protein for efficient cholesterol export. Either introducing single disulfide bonds to constrain … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The point mutants and deletion mutants of these loops exhibited declined cholesterol uptake and impaired trafficking compared to the wild-type NPC1L1, suggesting that the conformational transition of Loops 3-4 and 7-8 is essential to the function of NPC1L1. It is worth noting that, similar to the CLR-6 in the NPC1L1, a binding site for cross-linkable cholesterol is identified within Loop 7-8 of the homolog NPC1 by using clickable, photoreactive sterol probes in combination with quantitative mass spectrometry (37), and Loop 7-8 is indispensable for NPC1-mediated cholesterol export (23). Thus, it seems that NPC1L1 and NPC1 may sense the environmental cholesterol level alteration via the cytoplasmic Loops 3-4 and 7-8 of the SSD domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The point mutants and deletion mutants of these loops exhibited declined cholesterol uptake and impaired trafficking compared to the wild-type NPC1L1, suggesting that the conformational transition of Loops 3-4 and 7-8 is essential to the function of NPC1L1. It is worth noting that, similar to the CLR-6 in the NPC1L1, a binding site for cross-linkable cholesterol is identified within Loop 7-8 of the homolog NPC1 by using clickable, photoreactive sterol probes in combination with quantitative mass spectrometry (37), and Loop 7-8 is indispensable for NPC1-mediated cholesterol export (23). Thus, it seems that NPC1L1 and NPC1 may sense the environmental cholesterol level alteration via the cytoplasmic Loops 3-4 and 7-8 of the SSD domains.…”
Section: Discussionmentioning
confidence: 99%
“…The SSD-intervening loops (Loop TM1-TM2 , Loop TM3-TM4 , Loop TM5-TM6 , and Loop TM7-TM8 ) and the C-terminal cytoplasmic tail are located on the cytoplasmic side (16). The Loop TM7-TM8 was suggested to be an important element for cholesterol uptake (23), and the C-terminal cytoplasmic tail has been detected to have internalization motif for endocytosis (24). An internal tunnel that connects the extracellular domains to SSD was delineated in the structure of rat NPC1L1 (16) and also suggested in the structures of Niemann-pick C-related protein 1 (NCR1) (25), NPC1 (26), and Patched1 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Among the ABC transporters associated with cholesterol efflux ( Wang et al, 2008 ), many inductions were observed, suggesting increased efflux of cholesterol but with genotype specificities ( Figure 2B ; Supplementary Figure 1 ). Of note, Npc1 and Npc2 genes, which are involved in the transport of LDL-derived cholesterol from lysosomes to the cytoplasm ( Saha et al, 2020 ), were induced in Abcd2 −/− and Acox1 −/− cells while Npc1l1 , although weakly expressed, was repressed in every mutant genotype ( Figure 2B ; Supplementary Figure 1 ). The loss of these genes triggers endolysosomal accumulation of unesterified cholesterol and lipids and is associated to Niemann–Pick disease ( Vance, 2012 ).…”
Section: Resultsmentioning
confidence: 99%